Cohort Study of Downgraded Misdemeanor Convictions and Subsequent Violent Crime: Differences by Defendant Race and Ethnicity - Julia P. Schleimer, MPH; Miriam J. Haviland, PhD, MSPH; Amy Gallagher, MPH; Ayah Mustafa, BS; Rachel Ross, MPH; Garen Wintemute, MD, MPH; Deirdre Bowen, JD, PhD; Ali Rowhani-Rahbar, MD, PhD, MPH (Elsevier, 2024)
Introduction: Criminal convictions may be imperfect markers of criminalized behavior, in part because of criminal legal system processes (e.g., plea bargaining). In this retrospective cohort study of individuals convicted of misdemeanors, authors compared the risk of subsequent criminal charges for a violent crime among those initially charged with a felony with that among those initially charged with only misdemeanors, overall and by defendant race and ethnicity. Methods: The study population included individuals aged ≥18 years who were convicted of a misdemeanor in Washington Superior Courts from January 1, 2015 to December 31, 2019. Those with and without initial felony charges were age/gender matched in a 4:1 ratio. The primary outcome was the first subsequent violent crime charge in Washington Superior Courts through December 31, 2020. Data were analyzed with Fine-Gray hazard models from June 2022 to November 2023. Results: There were 3,841 individuals with initial felony charges and 956 with initial misdemeanor charges only. Median follow-up was 2.4 years for both groups. During follow-up, there were 166 new violent crime charges. In multivariable models, White defendants with initial felony charges had a greater risk of subsequent violent crime charges (subdistribution hazard ratio=2.58; 95% CI=1.24, 5.36) than White defendants with initial misdemeanor charges only. Among Black and Hispanic/Latinx defendants, initial felony versus misdemeanor charges were not associated with subsequent violent crime charges (subdistribution hazard ratio=0.93; 95% CI=0.44, 1.97 among Black defendants; subdistribution hazard ratio=0.49; 95% CI=0.15, 1.57 among Hispanic/Latinx defendants). Conclusions: Findings suggest differential associations between downgrading of felony charges to misdemeanor convictions and future violent crime charges by defendant race and ethnicity, with implications for inequitable collateral consequences of criminal convictions.